2021
DOI: 10.1039/d0ra09202a
|View full text |Cite
|
Sign up to set email alerts
|

Direct deposition of Sn-doped CsPbBr3 perovskite for efficient solar cell application

Abstract: All inorganic carbon-based planar perovskites, particularly CsPbBr3, have attracted considerable attention due to their excellent stability against oxygen, moisture, and heat for photovoltaic utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
(20 reference statements)
1
14
0
Order By: Relevance
“…As opposed to the previously reported CsPbBr 3 -based device structure, the given solar structure has higher J SC and FF values. It is seen that there are some differences between the calculated J sc and V oc values in the reported experimental results in the literature. ,, , The possible reason might be that our studied ETLs and HTLs are not matched with previously studied experimental ones ,, , as per their properties as well. Furthermore, optical properties also vary from absorber to absorber, which leads to solar energy absorption.…”
Section: Resultsmentioning
confidence: 59%
“…As opposed to the previously reported CsPbBr 3 -based device structure, the given solar structure has higher J SC and FF values. It is seen that there are some differences between the calculated J sc and V oc values in the reported experimental results in the literature. ,, , The possible reason might be that our studied ETLs and HTLs are not matched with previously studied experimental ones ,, , as per their properties as well. Furthermore, optical properties also vary from absorber to absorber, which leads to solar energy absorption.…”
Section: Resultsmentioning
confidence: 59%
“…In a recent study reported in 2021, Abib et al designed a novel deposition strategy for the stable phase Sn-substituted CsPbBr 3 perovskite alloy with efficient and economical carbon-based all-inorganic devices with the architecture of FTO/TiO 2 /CsPb 0.998 Sn 0.002 Br 3 /carbon. 132 This newly developed strategy allows direct thermal evaporation of the synthesized pristine and metal-doped perovskite powders on various types of ETLs. Similar to previous reports, adding Sn 2+ ions into perovskite precursors decreased the density of the pinholes and enlarged the grain size of the perovskite film.…”
Section: The Effects Of Various B-site Doping Ions In All-inorganic C...mentioning
confidence: 99%
“…Additionally, Ahmed et al used a precipitation method to apply it to PSCs capable of low temperature processes 14 and Qi et al applied powder engineering method in their study to fabricate a device with fewer defect 15 . Also, Jiang et al applied perovskite powder synthesis to the study of CsPbBr 3 ‐based solar cells 16 …”
Section: Introductionmentioning
confidence: 99%
“…15 Also, Jiang et al applied perovskite powder synthesis to the study of CsPbBr 3 -based solar cells. 16 All-inorganic perovskite is another important strategy for the commercialization of perovskite. It aims to improve the stability of perovskite by replacing thermally decomposable organic cation with stable inorganic cation in the A site.…”
Section: Introductionmentioning
confidence: 99%